PENGEMBANGAN ANTARMUKA PENGGUNA APLIKASI MEGA MALL BATAM CENTRE DENGAN MENGGUNAKAN METODE LEAN UX - Ardyanto Gunawan; Mesri Silalahi (Computer Science and Industrial Engineering, 2022)
Mega Mall Batam Centre is one of a large shopping centre located in Batam city. On May 6, 2021, Mega Mall Batam Centre introduced an application that can be accessed via smartphone devices that can be downloaded via Play Store and Appstore under the name Mega Mall Batam Centre. Some of the shortcomings of the application are the lack of clarity in the information conveyed, the points function available in the application only serves to increase member ratings without providing other uses. The purpose of this research is to develop the application user interface so that it can provide a high level of usability and provide a new experience to users. In developing the user interface of this application, the authors use the Lean UX design method as a tool during the UI/UX design phase, the prototyping development method as a tool during the research phase, and Figma as a prototyping application. With the development of the user interface of the application, can prove that application usage becomes more effective and efficient in obtaining the information presented, increases the aesthetic value of the application and has more opportunities to increase interest in using the application.